The development of phonological and reading skills in English and Afrikaans children - Cockcroft, Katherine Alexandra Sarah (My University, 1998)
Phonological awareness, or the ability to manipulate sounds, has been found to be highly correlated with the acquisition of reading skills. This awareness may be influenced by the orthography or language system in which the child is learning to read. In addition, different aspects of phonological awareness may also apply to different stages of reading development. This study found that depth of orthography does not seem to influence initial levels of phonological awareness. After two years of reading instruction, readers of a transparent orthography are better at phoneme segmentation and blending and reading nonwords than readers of an opaque orthography. Afrikaans children appear to begin leading in an alphabetic stage using a nonlexical strategy of grapheme-phoneme conversion. English beginner readers seem to start reading using predominantly a logographic strategy of visual word recognition. It also seems that some levels of phonological awareness such as onset/rime detection and syllable manipulation are acquired spontaneously by prereaders of both languages, but that the manipulation of phonemic units is dependent on the acquisition of literacy. The introduction of literacy training and/or the maturation of the children's phonological systems results in a change to a greater awareness of small phonemic units than larger units.
A dissertation submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts.
Keywords: Phonetics; Sound symbolism; English language--South Africa; Afrikaans language--Study and teaching; Language and languages--Phonemics; Reading (Primary); Children--South Africa--language